A clinical case report and literature review of the 3q29 microdeletion syndrome. Issue 3 (July 2015) - Cox, Devin M.; Butler, Merlin G.
<x xml:space="preserve">Abstract</x> We report on a 15-year-old male with the 3q29 microdeletion syndrome and summarize the medical literature. He had intellectual disability, autism spectrum disorder, anxiety, obsessive compulsive tendencies, speech delay, delayed walking, a hypernasal voice, gait abnormalities, chronic constipation, gastroesophageal reflux disorder, urinary voiding dysfunction, abnormal skin pigmentation, and dysmorphic features. We present a review of the literature for the 3q29 microdeletion syndrome by comparing both the phenotype and the genetic defects in reported cases. Of the 38 previously reported cases with deletion size information, the most common chromosome deletion was 1.6 Mb in size including ∼30 genes. This emerging microdeletion syndrome is characterized by intellectual disability, speech delay, behavioral problems, craniofacial dysmorphism, and musculoskeletal abnormalities.